The law relating to orders of surcharge against public servants and employees of statutory bodies - Faruqi, Shad Saleem (Pejabat Penasihat Undang-Undang, 2016)
Public office is a public trust. This is especially so in the matter of handling the nation’s or the public’s money. The law on surcharge refers to the penalty imposed on a fiduciary for breaching his fiduciary duty.